3D‐printable cyclic peptide loaded microporous polymers for antimicrobial wound dressing materials. (8th December 2022) - Thum, Matthew D.; Lu, Qin; Stockmaster, Kalib T.; Haridas, Dhanya; Fears, Kenan P.; Balow, Robert B.; Lundin, Jeffrey G.
Abstract: Multifunctional wound dressings deliver numerous complementary therapeutics in a single, easy‐to‐use material; however, incompatibilities between additives and the inability to control spatial loading (i.e., surface vs. bulk) sometimes complicate material design and inhibit the use of all available beneficial additives. 3D printing affords the capability to fabricate polymeric wound dressings in unique and individually specific morphologies, as well as the ability to control spatial composition of the multifunctional wound dressing to overcome some of the aforementioned shortfalls from traditional material fabrication techniques. We demonstrate 3D printing as a viable tool to place additives from novel class of antimicrobials, cyclic peptides, in a UV curable, and multifunctional (absorbent and hemostatic) microporous polymer. Microscopic and material characterization confirmed loading of cyclic peptide and microporous architecture was unaffected by peptide loading and the extrusion 3D printing process. Cytotoxic evaluations indicate toxicity of peptide additives toward prokaryotic and eukaryotic cells and highlight the importance of spatial control afforded by 3D printing. The robustness of high internal phase emulsion templating and 3D printing was confirmed with antimicrobial assays that showed antimicrobial efficacy of the cyclic peptides were maintained and unaffected by polymerization and processing.